Intestinal Giardiasis Disguised as Ulcerative Colitis - Yu Zhen; Lin Liao; Hu Zhang (Case Reports in Gastrointestinal Medicine)
Parasite-associated colitis is quite rare in clinical practice of Ulcerative Colitis (UC). Here we reported an intestinal giardiasis case that has been diagnosed with UC. Further examination of stool revealed cysts of Giardia. This case completely responded to Albendazole. Giardiasis should be included for the differential diagnosis of UC.